Complex Odontoma in Both the Jaws: A Rare Case Report - Srivastava, Adit; Annaji, AG; Nyamati, Sanjay B; Singh, Govind; Shivakumar, GC; Sahana, S (Journal of Orofacial Research, 2012)
Odontomas are the most common odontogenic tumors. They are usually asymptomatic and are often discovered during routine radiography. Complex odontomas appear as irregular calcified masses that bear no similarity to teeth. We report a rare case of complex odontoma in maxilla and mandible in an adult patient with clinical, radiological, histological features and treated surgically, with its review of the literature.